Moths of Western North America 3. Distribution of Arctiidae of Western North America. Part 1. Text, maps, and references - Ferguson, Douglas C., author; Opler, Paul A., author; Smith, Michael J., author; Donahue, Julian P., author; C.P. Gillette Museum of Arthropod Diversity, publisher (Colorado State University. Libraries, 2000)
This is the third of a series of atlases detailing the distributional occurrence of the moths of western North America. Part 1 of the atlas of western Arctiidae covers the documented distribution of a group of Lepidoptera with many well-known and brightly colored species. Yet despite their bright colors the taxonomic relationships in some genera are unclear and there are undescribed North American species in at least four genera (Crambidia, Euchaetes, Holomelina, and Grammia).
Distribution of Arctiidae of Western North America. Part 1. Text, maps, and references
Keywords: Arctiidae -- West (U.S.) -- Geographical distribution; Arctiidae -- Canada, Western -- Geographical distribution; Arctiidae -- Mexico, North -- Geographical distribution; Arctiidae -- West (U.S.) -- Maps; Arctiidae -- Canada, Western -- Maps; Arctiidae -- Mexico, North -- Maps